2017
DOI: 10.1175/jhm-d-16-0109.1
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid LSSVM Model with Empirical Mode Decomposition and Differential Evolution for Forecasting Monthly Precipitation

Abstract: In this study, a hybrid least squares support vector machine (HLSSVM) model is presented for effectively forecasting monthly precipitation. The hybrid method is designed by incorporating the empirical mode decomposition (EMD) for data preprocessing, partial information (PI) algorithm for input identification, and differential evolution (DE) for model parameter optimization into least squares support vector machine (LSSVM). The HLSSVM model is examined by forecasting monthly precipitation at 138 rain gauge stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In general, local precipitation is influenced by complex interactions of ocean, atmosphere, and land surface processes, which leads to the result that the physical mechanisms for change in precipitation are complicated (O'Gorman and Schneider, 2009; Tao et al ., 2017). However, the climate indices combining information about the oceans and the atmosphere can provide key information about long‐term precipitation, so they have been recognized as the most important factors influencing on the generation of extreme precipitation (Wang and Yan, 2011; Wang and Yang, 2016; Limsakul and Singhruck, 2016; Kim et al ., 2018; Tong et al ., 2019; Jiang et al ., 2019; Chen et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, local precipitation is influenced by complex interactions of ocean, atmosphere, and land surface processes, which leads to the result that the physical mechanisms for change in precipitation are complicated (O'Gorman and Schneider, 2009; Tao et al ., 2017). However, the climate indices combining information about the oceans and the atmosphere can provide key information about long‐term precipitation, so they have been recognized as the most important factors influencing on the generation of extreme precipitation (Wang and Yan, 2011; Wang and Yang, 2016; Limsakul and Singhruck, 2016; Kim et al ., 2018; Tong et al ., 2019; Jiang et al ., 2019; Chen et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The multi‐resolution analysis methods including wavelet transform (WT) and empirical mode decomposition (EMD) have been widely used to decompose the original time series into various simpler components to extract meaningful information (Napolitano et al ., 2011; He et al ., 2014; Tao et al ., 2017). However, the application of WT demands the choice of basis functions, requiring considerable skill in their selection and application (Huang et al ., 2014; Tao et al ., 2017). The EMD as another non‐stationary data analysis method is based on the principle of local scale separation and does not require any predetermined basis functions (Karthikeyan and Nagesh Kumar, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This method has also been used to solve game theory optimal projection (GTOP). Furthermore, Tao et al (2017) forecasted monthly precipitation at 138 rain gauge stations in the Yangtze River basin by implementing a hybrid least squares support vector machine (HLSSVM) model. At the same time, the LSSVM-DE was built to provide a comparison tool by combining the LSSVM and differential evolution (DE).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, this study aims to develop a high-performance hybrid machine learning model for modeling the Mr using LSSVM. Although the hybrid LSSVM models outperform single LSSVM and SVM, the method in modeling nonlinear problems 32 , its use in modeling Mr is still limited. Hybrid LSSVM was applied in different engineering applications, and that performance is shown to be high 24 , 32 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the hybrid LSSVM models outperform single LSSVM and SVM, the method in modeling nonlinear problems 32 , its use in modeling Mr is still limited. Hybrid LSSVM was applied in different engineering applications, and that performance is shown to be high 24 , 32 34 . For instance, LSSVM- particle swarm optimization (PSO) was proposed to model slope stability, and the results showed that the performance of the model was high 35 .…”
Section: Introductionmentioning
confidence: 99%